Extent and distribution of CPP deposits in patients affected by calcium pyrophosphate dihydrate deposition disease: an ultrasonographic study. Issue 11 (26th March 2013) - Filippou, Georgios; Filippucci, Emilio; Tardella, Marika; Bertoldi, Ilaria; Di Carlo, Marco; Adinolfi, Antonella; Grassi, Walter; Frediani, Bruno
Abstract : Objective: To assess the extent of calcium pyrophosphate dihydrate (CPP) crystal deposition and the distribution of affected sites, using ultrasonography (US), in patients affected by CPP deposition disease (CPPD). Patients and methods: 42 consecutive patients affected by definite CPPD according to the McCarty criteria were enrolled in the study. All patients underwent an US examination of metacarpophalangeal joints of II, III, IV and V fingers of both hands, wrists and knees, Achilles' tendons and plantar fascia looking for CPP deposits. A dichotomous score for presence/absence of CPP and a semiquantitative score for extent of deposits (0–3: 0, absent; 1, 1–2 spots; 2, more than two spots covering <50% of the structure; 3, deposits covering >50% of the structure) were assigned to each site examined. A site distribution score (total number of affected sites) was then calculated as well as an extent score equal to the sum of the extent scores of all sites. Results: The mean involvement in our patients was 4.7 sites (SD±1.7, range 2–8 sites). The knee was the most affected, site (41 of 42) followed by the wrist (at least one in 37 patients) the Achilles' tendons (23 patients), plantar fascia (11 patients) and metacarpophalangeal joints (four patients). The highest mean values of the extent score were in the menisci, followed by the hyaline cartilage of the femoral condyles and the entheses. Conclusions: The deposition of CPP crystals involves at least two sites with a mean of four sites involved in most patients affected by CPPD and is therefore an oligoarticular or polyarticular disease.